Boundaries - Doh, Emmanuel Fru (Book collections on Project MUSE., 2015)
In Boundaries, Musang, from the Grassfields, falls in love with Etonde from the Coast. Although aware of some existing tension and unfounded mistrust between both camps, the couple is ready to marry when Etonde's father, incredibly, rejects the marriage proposal at the last minute. Although traumatized, Musang, finally, deems the rejection a sign from heaven and so reconsiders a lingering vocation idea - the priesthood. Meanwhile, a devastated Etonde, now defiant of men, struggles on to regain her equilibrium. Years after, however, and barely months away from his ordination into the priesthood, Musang, an exemplary postulant, is suddenly given the deprecating choice to go on probation or leave the seminary; he leaves.